PENGARUH MANAJEMEN LABA TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI - Hernadianto Hernadianto; Ade Oktarina (Universitas Muhammadiyah Bengkulu, 2021)
ABSTRACTÂ High corporate values can increase the prosperity of shareholders so that they will invest their capital into the company's stock which causes the company's management to practice earnings management and can be overcome or minimized with its own supervision through corporate governance. For that we need research about the effect of earnings management on corporate value with corporate governance as a moderator variable. Based on the background of the above problem, the formulation of the problem in this research is What profit management affects corporate value, corporate governance with managerial ownership ownership, institutional ownership, proportion of independent board of commissioners, audit quality affect the relationship between earnings management to corporate value? The purpose of this research is to prove the influence of earnings management on corporate value, corporate governance with managerial ownership, institutional ownership, proportion of independent board of commissioner, audit quality to the relationship between earnings management to company value at manufacturing company in Indonesia Stock Exchange.Â This research uses quantitative method and the data used is secondary data which is financial report of manufacturing company in Bursa Efek Indonesia during period 2013-2015. The sample in research using purposive sampling method, found 40 companies that enter the criteria. Hypothesis testing is done by using multiple linear regression analysis to test the simultaneous influence of sever The results prove that earnings management can raise the value of the company. The moderating variables that affect the relationship of earnings management to firm value are managerial ownership and institutional ownership. While the proportion of independent board of commissioners, and audit quality is not a moderating variable.Â Keywords:Earnings management, corporate value, corporate governance, managerial ownership, institutional ownership, proportion of independent board of commissioners, audit quality al independent variables on one dependent variable.